Caractéristiques Physico-Chimiques Des Eaux De La Nappe Alluviale De La Vallée Du Goulbi N'Kaba Dans La Région De Maradi Au Niger - Laoualy Yahouza; Sandao Issoufou; Maman Sani Abdou Babaye; Bruno Metral; Boureima Ousmane (European Scientific Journal, ESJ, 2018)
The Goulbi N'Kaba valley is located in the Maradi region of southcentral Niger. It contains an alluvial aquifer that is used for the drinking water supply, breeding, increasingly more irrigation and for the extractive industries. In addition, this valley is subject to the effects of climate change. A study is needed to improve the knowledge of this water resource, a condition for a better match between the uses and the potentialities of the aquifer. The investigations on the physicochemical parameters and the stable isotopes of the water molecule (oxygen 18 and deuterium), made it possible to reach the following main results: The waters of the alluvial aquifer are slightly acidic, with a pH ranging from 5,2 to 7.2. The mineralization is relatively weak with conductivities between 89,3 and 325 μs/cm, resulting in sodium and calcium bicarbonate facies. These waters are generally good for human consumption and for irrigation. However, in the center of the study area, fluorine and nitrate contents are observed that exceed the WHO guideline values (2006).